2007
DOI: 10.1136/hrt.2007.116616
|View full text |Cite
|
Sign up to set email alerts
|

Implantable loop recorder in unexplained syncope: classification, mechanism, transient loss of consciousness and role of major depressive disorder in patients with and without structural heart disease

Abstract: The presence of SHD has little predictive value for the occurrence or type of arrhythmia in patients with unexplained syncope. Patients with major depressive disorder are prone to early recurrence of symptoms and have no evidence of arrhythmia in most cases. The ILR leads to specific treatment in half of all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 37 publications
1
23
2
2
Order By: Relevance
“…Pezawas et al reported an even greater prevalence of recurrent symptoms (91%) but only 39.4% presented an arrhythmia during the event (mostly bradycardia), without episodes of ventricular tachycardia. 19 We obtained a final diagnosis in 28.2% of the present group, mainly secondary to bradycardia-related events, similar to that reported by ISSUE2 and Entem et al 7,13 One-third of the BBB cohort had a final diagnosis, with a greater rate in those patients without previous EPS, likely because some of the high-risk patients would have been previously diagnosed if the test had been performed. In 2 previous series of patients with syncope, BBB, and negative EPS, the rates of final diagnosis were 36.5% 6 and 45%, 8 mostly brady-…”
Section: Subgroup Analysissupporting
confidence: 70%
“…Pezawas et al reported an even greater prevalence of recurrent symptoms (91%) but only 39.4% presented an arrhythmia during the event (mostly bradycardia), without episodes of ventricular tachycardia. 19 We obtained a final diagnosis in 28.2% of the present group, mainly secondary to bradycardia-related events, similar to that reported by ISSUE2 and Entem et al 7,13 One-third of the BBB cohort had a final diagnosis, with a greater rate in those patients without previous EPS, likely because some of the high-risk patients would have been previously diagnosed if the test had been performed. In 2 previous series of patients with syncope, BBB, and negative EPS, the rates of final diagnosis were 36.5% 6 and 45%, 8 mostly brady-…”
Section: Subgroup Analysissupporting
confidence: 70%
“…Отсутствие документированной аритмии во время синкопе позволяет исключить аритмию, как механизм обмо-рока [246]. У пациентов >40 лет с повторным обморо-ком, без значительной органической патологии серд ца и нормальной ЭКГ, аритмия, обычно асисто-лия, присутствует во время обморока в 50% [247][248][249][250].…”
Section: другие симптомыunclassified
“…The ILR is implanted subcutaneously in the left hemithorax with automatic and patient-activated ECGdocumentation modes available on most devices. Many studies have shown its value in detection of infrequent arrhythmias [39][40][41] . Current guidelines suggest ILR implantation for unexplained syncopes.…”
Section: The Implantable Loop Recordermentioning
confidence: 99%